2017
DOI: 10.1073/pnas.1605946114
|View full text |Cite
|
Sign up to set email alerts
|

Hearing regulates Drosophila aggression

Abstract: Aggression is a universal social behavior important for the acquisition of food, mates, territory, and social status. Aggression in Drosophila is context-dependent and can thus be expected to involve inputs from multiple sensory modalities. Here, we use mechanical disruption and genetic approaches in Drosophila melanogaster to identify hearing as an important sensory modality in the context of intermale aggressive behavior. We demonstrate that neuronal silencing and targeted knockdown of hearing genes in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 48 publications
3
32
0
Order By: Relevance
“…A recent study (76) further reported that AS promote aggression, while CSs inhibit aggressive interactions between Drosophila males. In order to test whether Dnlg2- and Dnlg4-deficient flies react appropriately to sound signals, we extended the competitive courtship paradigm by continuous stimulation with WN, CS, or aggression sounds.…”
Section: Resultsmentioning
confidence: 94%
“…A recent study (76) further reported that AS promote aggression, while CSs inhibit aggressive interactions between Drosophila males. In order to test whether Dnlg2- and Dnlg4-deficient flies react appropriately to sound signals, we extended the competitive courtship paradigm by continuous stimulation with WN, CS, or aggression sounds.…”
Section: Resultsmentioning
confidence: 94%
“…Although the precise mechanism by which this polymodal information is integrated is still unclear, anatomical and functional studies point to the P1 neurons in the brain as candidates for mediating sensory integration and behavioral action selection . A related, sexually‐dimorphic social behavior, aggression, is also modulated by chemical and auditory signals . Interestingly, integration of these cues may also occur in P1 neurons , raising the question of how these central neurons are differentially regulated to trigger alternative behaviors.…”
Section: Neural Circuit Integration Of Chemosensory and Mechanosensormentioning
confidence: 99%
“…These reports indicate that aggression and hearing are possibly interlinked. Previous reports have shown various sensory modalities in mediating of aggressive behavior in Drosophila melanogaster including olfactory, gustatory, as well as visual neural networks [6]. Furthermore it was found that, neuronal silencing and targeted knockdown of hearing genes such as d trpl (transient receptor potential-like) and the Ca2+ signaling-related genes Arr2 and inaD in the fly's auditory organ elicit abnormal aggression [6].…”
Section: Introductionmentioning
confidence: 99%
“…Hearing as a sensory modality in the context of aggressive behavior has been shown to play a major role in controlling behavior [6]. Precise integration and processing of sensory inputs are crucial to evoke a suitable behavioral response [7].…”
Section: Introductionmentioning
confidence: 99%